2015
DOI: 10.1136/bmjopen-2014-005306
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug use in adolescents born with an orofacial cleft: a population-based study

Abstract: ObjectivesBeing born with an orofacial cleft (OFC) can, due to an incomplete closure of the lip and/or palate, convey a deviant speech and/or deviant facial aesthetics, which may in turn increase the risk for poor psychological health later in life. Previous investigations have been based on small samples and self-reports, not distinguishing between the three different types of OFC: cleft lip (CL), CL and palate (CLP) and cleft palate only (CPO). We present a large population-based study, considering psychotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
2
11
2
Order By: Relevance
“…7 Frequencies of alcohol consumption during pregnancy slightly lower than in the present study (22.5%) were reported by Campos Neves et al 6 (17.2%) and by Bezerra et al 37 (15%), both for the Brazilian population. A frequency of smoking higher than that observed in the present study (11.6%) was found by Nilsson et al 38 in a study of Swedish children with CL/P, in which 23% of the mothers reported cigarette smoking during pregnancy. A 45% frequency of pregnant women who smoked at any time during pregnancy was found by Little et al 39 in a study with 190 CL/P patients from Scotland and England.…”
Section: Discussioncontrasting
confidence: 81%
“…7 Frequencies of alcohol consumption during pregnancy slightly lower than in the present study (22.5%) were reported by Campos Neves et al 6 (17.2%) and by Bezerra et al 37 (15%), both for the Brazilian population. A frequency of smoking higher than that observed in the present study (11.6%) was found by Nilsson et al 38 in a study of Swedish children with CL/P, in which 23% of the mothers reported cigarette smoking during pregnancy. A 45% frequency of pregnant women who smoked at any time during pregnancy was found by Little et al 39 in a study with 190 CL/P patients from Scotland and England.…”
Section: Discussioncontrasting
confidence: 81%
“…Our finding of increased use of psychotropic medications by individuals with CP is consistent with the recent study from Sweden focused on adolescents (Nilsson et al, ). That study also reported increased use among individuals with CL but not those with CLP.…”
Section: Discussionsupporting
confidence: 92%
“…Additional models were stratified by gender (because of variation in prevalence of mental health disorders and treatment use between male and female subjects), age group (0–34 and 34–76 years), and birth cohort (1936–1975 and 1976–2009). Furthermore, because a recent Swedish register‐based study on use of psychotropic medications in individuals with OC focused on adolescents (Nilsson et al, ) and many studies focus primarily on children (Hunt et al, ; Murray et al, ; Wehby et al, ; Tyler et al, ), we also restricted analyses to the children and adolescent (aged 0–17 years). Additionally for the outcomes with significant findings, additional analyses were stratified by severity, including separating unilateral and bilateral status for CLP; submucous, soft palate only, or soft and hard palate for CP; and cleft laterality (left‐sided vs. right‐sided) for unilateral CLP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Recently, a large Swedish population-based study showed that CL and CPO increase the risk for psychotropic drug use in adolescence; however, there was no distinction made among the different groups of psychotropic drugs or psychiatric indications. 19 The majority of previous studies are small, underpowered, and clinically based, and focus on psychological symptoms rather than psychiatric disorders as a medical diagnosis.…”
mentioning
confidence: 99%